Three-Dimensional Evaluation of Dental Arches in Individuals with Syndromic Craniosynostosis - Pinto, Rayane De Oliveira [UNESP]; Tonello, Cristiano; Peixoto, Adriano Porto; De Jesus, Adriana Souza [UNESP]; Santos-Pinto, Ary Dos [UNESP]; Raveli, Dirceu Barnabé [UNESP] (Hindawi, 2023)
Objective. Individuals with syndromic craniosynostosis present alterations in the dental arches due to anomalies caused by the early fusion of the craniomaxillary sutures. This study aimed to compare intradental and interdental dimensions between individuals with Apert and Crouzon syndromes and nonsyndromic controls. Materials and Methods. Digital models were obtained from the archive of a public tertiary care hospital. The sample consisted of 34 patients (Apert n = 18, Crouzon n = 16) and 34 nonsyndromic controls matched for gender and age. Measurements of perimeter, length, intercanine and intermolar distances (upper and lower), overjet, and molar ratio were performed. Statistical comparisons were performed using ANOVA and Tukey tests p<0.05. Results. Patients with Apert and Crouzon syndromes have severely reduced maxillary transverse dimensions, perimeter, and length of the upper arch compared to the control group p<0.001. The lower arch is less impacted. Patients with Apert syndrome had an anterior crossbite p<0.001, while patients with Crouzon syndrome had an edge-to-edge bite p< 0.011. Patients with Apert and Crouzon syndromes do not have serious transverse proportion problems when comparing the upper and lower arches. Conclusions. In this sample, both the Apert and Crouzon groups have severely compromised upper arches compared to the control group. Mild dentoalveolar expansion in the maxilla should be sufficient for the transverse adaptation of the dental arches before frontofacial advancement.